ANALISIS DETERMINAN JUMLAH TEMUAN PEMERIKSAAN LAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA (Studi atas Laporan Keuangan Pemerintah Provinsi Tahun Anggaran 2011 - 2014 di Indonesia) - Imron Kamil; Dwi Ratmono (Diponegoro Journal of Accounting, 2016)
This research aims to analyze the determinants of audit finding numbers issued by Supreme Audit Board on financial report of provinces in Indonesia. Independent variables in this research is size, opinion, performance score, and complexity. Size is measured by realized of revenue while opinion is measured by dummy variable. One for unqualified opinion, zero for others. Performance score refers to Ministry of Domestic Affairs Determination. Whereas complexity is measured by numbers of units of work.Population of this research is all Provincial Government in Indonesia. Purposive sampling method is using to take the samples so it takes 124 financial report fiscal year 2011 - 2014 to use as data research. Method for testing the hypothesis in this research was conducted using multiple linear regression. The results show that size and previous-year opinion have significant effect to audit finding numbers. Size makes a positive influence to audit finding numbers while opinion makes negative influence. This research also shows that complexity and performance score have no effect to audit finding numbers.